8.2k views
1 vote
7b - 3 = 6b + 4 how do I solve it for B

2 Answers

3 votes

Answer:

b = 7

Explanation:

7b - 3 = 6b + 4

1. subtract 6b on both sides of the equation

b - 3 = 4

2. add 3 to both sides

b = 7

User Thehiatus
by
5.1k points
7 votes

Answer: b = 7

Step-by-step explanation: When we have his kind of a setup, we want to put our variables together on one side of the equation and our numbers together on the other side of the equation.

So first, let's put our variables together on the left

side by subtracting 6b from both sides of the equation.

That gives us b - 3 = 4

Now we can move our numbers to the right by

adding 3 to both sides and we get b = 7.

So we have b = 7 which is the solution to this equation.

User Brady Dowling
by
5.3k points